أثر القنوات الفضائية في التنشئة السياسية والاجتماعية لدى طلاب كلية التربية "دراسة ميدانية (Economic studies journal, 2018)
The objective of this paper is to identify the impact of satellite television channels on the social and political upbringing of the students within the Faculty of Education. The sample selected for this research was consisted of (79) students who are invited from different academic disciplines. However, the analytical descriptive method was used for this research. Based on this method, the author sought to identify, interpret and evaluate the results of statistical analysis. Interestingly, this research found that:• Programs shown on satellite TV channels have negative impact on the social fabric of society• Satellite TV channels were found to have contribution in changing the political trends among the audience• Satellite TV channels have an effective impact on the behavior of the followers through the programs presented• Satellite TV channels may show some programs that lead to cultural invasion• Satellite TV channels are an effective mean to assert political pluralismThe programs offered by satellite TV channels are not sufficient to develop the political culture of the followers.
Keywords: satellite channels; political upbringing.